2008
DOI: 10.1021/ja076557x
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+-Free Bacillus stearothermophilus Tryptophanyl-tRNA Synthetase Retains a Major Fraction of the Overall Rate Enhancement for Tryptophan Activation

Abstract: Few experimental data are available for rates of enzymatic phosphoryl-transfer reactions in the absence of the divalent metal ions associated with such reactions. Such data are of interest for amino acid activation by class Ic aminoacyl-tRNA synthetases, for which there is substantial evidence that binding energy of ATP may account for a major fraction of the overall rate enhancement, and it is crucial to know if these effects themselves depend on the divalent metal ion. We describe a nested, non-linear model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…The stunning quantitative agreement between the coupling energies estimated from multi-mutant and modular combinatorial experiments with those anticipated from the characterization of metal-free catalysis 25 reinforces our earlier suggestions 32,34,38,66 that domain motions are necessary to form the TrpRS·transition state complex, and hence that differences observed between TrpRS crystal structures are relevant to the catalytic cycle. Thus, the different TrpRS crystal structures probably approximate those states connected by motions necessary for transition-state stabilization.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The stunning quantitative agreement between the coupling energies estimated from multi-mutant and modular combinatorial experiments with those anticipated from the characterization of metal-free catalysis 25 reinforces our earlier suggestions 32,34,38,66 that domain motions are necessary to form the TrpRS·transition state complex, and hence that differences observed between TrpRS crystal structures are relevant to the catalytic cycle. Thus, the different TrpRS crystal structures probably approximate those states connected by motions necessary for transition-state stabilization.…”
Section: Resultssupporting
confidence: 83%
“…Prompted by the suggestion that the TrpRS catalysis should be essentially eliminated in the absence of Mg 2+ ion, we prepared extensively depleted stocks of enzyme, assay buffer, and reagents 25 . The resulting assays exhibited reduced, but still substantial rate accelerations over the uncatalyzed rate, which we initially attributed to residual remaining Mg 2+ ion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanistic studies on intact TrpRS had previously identified a profound intramolecular coupling, ΔΔG ‡ ~ − 5 kcal/mole necessary for catalytic assist by the active-site Mg 2+ ion [92] and achieving full catalytic proficiency by the full-length enzyme [89,32,93,92]. A five-way coupling interaction, ΔΔG ‡ ~ − 5kcal/mole, was also measured between four residues in an allosteric switching region 20 Å from the active-site metal that mediates the shear involved in domain movement during catalysis [94].…”
Section: Evidence For Bi-directional Coding Ancestry: Molecular Pmentioning
confidence: 99%